Cardiac Arrhythmias at High Altitude. Issue 1 (1st March 2011) - Woods, David; Boos, C; Roberts, PR
Abstract : Palpitations at high altitude have been experienced, but seldom recorded, for centuries. The hypoxia, sympathetic activation and alkalosis of altitude predispose to cardiac ischaemia and arrhythmia. Indeed, sudden cardiac death is responsible for 30% of all deaths during mountain sports at altitude. This article reviews the literature to date on the evidence for cardiac arrhythmias at altitude.